POSTPARTUM CARE IN CENTRAL JAVA TRADITION - Rahmawati, Ita (Proceedings of the International Conference on Applied Science and Health, 2017)
The puerperal period is a critical period. 60% of maternal deaths occur after deliveryÂ and 50% of them occur in the first 24 hours. The high rate of maternal and child mortality in Indonesia is closely related to social and cultural factors, particularly the Java community. During the postpartum, Abstinence / or postnatal care suggestion is usually associated with the physical condition of the recovery process.